2018
DOI: 10.1111/cbdd.13353
|View full text |Cite
|
Sign up to set email alerts
|

A panoptic uncovering of the dynamical evolution of the Zika Virus NS5 methyltransferase binding site loops—zeroing in on the molecular landscape

Abstract: The global threat of the Zika virus to humanity is real. Innovative and potent anti-Zika virus drugs are still at large, due to the lack of anti-Zika virus drugs that have passed phase 1 trials. Experimental research has revealed novel inhibitors of Zika virus NS5 methyltransferase enzyme. This study has taken a step further to provide insight into the molecular dynamics of Zika virus and inhibitor binding, which have not been established experimentally. Movements of the methyltransferase binding site loops ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Thermodynamic calculations provide quantitative mechanistic insights into the binding profile of p38⍺ MAP kinase inhibitors. The binding free energies of the SB203580, NDPPC, and NCT503 binding at the p38⍺ MAP kinase (N-terminal domain) site were calculated using the Molecular mechanics with the generalized Born/Poisson-Boltzmann and surface area solvation (MM/PBSA) method provided in the AMBER14 package (Devnarain & Soliman, 2018;Genheden & Ryde, 2015). Our MM/PBSA calculations showed that the compounds exhibited considerably favorable negative energies, indicating strong and high-affinity binding (Table 1).…”
Section: Thermodynamics Analysis Of the Interaction With The P38⍺ Mapkmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermodynamic calculations provide quantitative mechanistic insights into the binding profile of p38⍺ MAP kinase inhibitors. The binding free energies of the SB203580, NDPPC, and NCT503 binding at the p38⍺ MAP kinase (N-terminal domain) site were calculated using the Molecular mechanics with the generalized Born/Poisson-Boltzmann and surface area solvation (MM/PBSA) method provided in the AMBER14 package (Devnarain & Soliman, 2018;Genheden & Ryde, 2015). Our MM/PBSA calculations showed that the compounds exhibited considerably favorable negative energies, indicating strong and high-affinity binding (Table 1).…”
Section: Thermodynamics Analysis Of the Interaction With The P38⍺ Mapkmentioning
confidence: 99%
“…The integrated CPPTRAJ and PTRJ modules implemented in AMBER18 were used to generate the output coordinates and printed trajectories (Roe & Cheatham, 2013). The visual analysis of structures was performed using combined graphical interfaces of the UCSF Chimera (Yang et al, 2012), Molegro Molecular Viewer (Devnarain & Soliman, 2018), and BIOVIA Discovery Studio (A. T. Adewumi et al, 2022). Lastly, the data were processed with MicroCal Origin-6.0 data software (Seifert, 2014).…”
Section: Molecular Dynamics Simulations and Thermodynamics Calculationmentioning
confidence: 99%
“…It is an imperative method used to determine the in-depth binding mechanism of the receptor-ligand interacting systems. Here, we used the BFE with the MM/GBS technique to estimate the binding affinity within the docked Ag85C-CyC 8b system to gain insights into their binding landscape (Devnarain & Soliman, 2018). Thus, we employed this approach to calculate the binding free energies of the inhibitor CyC 8b modelled in the open conformation using 35,000 snapshots generated from the 350 ns trajectories.…”
Section: Thermodynamic Calculationsmentioning
confidence: 99%
“…This protein has two functional domains: an N -terminal, which possess methyltransferase (MTase) activity promoting RNA capping and a C -terminal with RNA polymerase (RdRp) activity . NS5MTase has four residues in the active site (Lys61–Asp146–Lys182–Glu218), which promotes the addition of methyl groups at N-7, 2′O positions of RNA and the 2′-O-ribose position of adenosines of RNA from an S-adenosyl- l -methionine (SAM) methyl (CH 3 ) group donor . Viral RNA methylation mechanisms differ from those of the host and have been reported as essential improvement genomic stability and evasion of the host’s innate immune system during the flaviviral replicative cycle. , …”
Section: Introductionmentioning
confidence: 99%
“…12 NS5MTase has four residues in the active site (Lys61−Asp146−Lys182−Glu218), which promotes the addition of methyl groups at N-7, 2′O positions of RNA and the 2′-O-ribose position of adenosines of RNA from an S-adenosyl-L-methionine (SAM) methyl (CH 3 ) group donor. 13 Viral RNA methylation mechanisms differ from those of the host and have been reported as essential improvement genomic stability and evasion of the host's innate immune system during the flaviviral replicative cycle. 14,15 Structure-based virtual screening (SBVS), molecular docking, dynamics simulation (DM), and QM/MM (quantum mechanics/molecular mechanics) have been used as tools for the identification of promising drugs.…”
Section: ■ Introductionmentioning
confidence: 99%